Revitalisasi Tujuan Pendidikan Islam dalam Masyarakat Multikultural: Studi Filosofis dan Pedagogis - Darun Mutammimah; Syarif, Zainuddin; Inayati, Mahfida; Kamilia, Dina (Kartika: Jurnal Studi Keislaman, 2025)
Islamic education has the main objective of forming faithful, knowledgeable, and noble human beings. However, in the context of a multicultural society, Islamic education faces challenges in instilling the values ​​of diversity without eliminating the essence of Islamic teachings. This article aims to analyze philosophically and pedagogically how Islamic education can be revitalized to remain relevant in a heterogeneous society. Using a qualitative method based on literature studies, this study examines the concept of human ontology in Islam, multicultural values ​​in the Qur'an and hadith, and strategies for implementing inclusive Islamic education. The results of the study show that Islam conceptually teaches the principles of tolerance, social justice, and harmonious life in diversity. However, in practice, Islamic education still tends to be homogeneous and does not accommodate the dynamics of multiculturalism. Therefore, the revitalization of Islamic education can be done through the integration of the Islamic educational philosophy approach with multicultural pedagogy, updating the curriculum to be more inclusive, and strengthening the role of educators in instilling an attitude of tolerance and openness. With this strategy, Islamic education can become an instrument that not only forms religious and moral individuals, but also builds a harmonious, just, and democratic society in diversity.